Pseudorandom ultrasonic Doppler meter of liquid flow and profile with digital serial signal processing - TRAWIŃSKI, Z.; CATHIGNOL, D. J. (Archives of Acoustics, 1990)
This paper presents a new method and new ultrasonic device for "real-time" measuring velocity profiles of liquid flow in vessel. Previously a flowmeter with pseudorandom coding of the transmitted signal made it possible to measuring point on a precisely determined depth with respect to the position of the ultrasonic probe. In order to obtain data for the entire penetration depth of the ultrasonic beam with that method, a system consisting or so many delay-receiving systems as there is measuring points, in which we need data for, would have be built. While the presented original method only one transmitting-recciving system, enabling a measurement in all measuring points independently and at the same time.